Ready-to-wear and ready-to-work : a century of industry and immigrants in Paris and New York - Green, Nancy L. (Comparative and international working-class history., 1997)
Nancy L. Green offers a critical and lively look at New York's Seventh Avenue and the Parisian Sentier in this first comparative study of the two historical centers of the women's garment industry. Torn between mass production and ""art, "" this industry is one of the few manufactauring sectors left in the service-centered cities of today. Ready-to-Wear and Ready-to-Work tells the story of urban growth, the politics of labor, and the relationships among the many immigrant groups who have come to work the sewing machines over the last century. Green focuses on issues of fashion an